Photo-curing hyaluronic acid-Janus antibacterial packs as O2 generator precisely modulate the infectious microenvironment for antibiotic-free periodontal therapy - Runxiu Wei; Gaojie Li; Yuying Huang; Linjing Mi; Jiamin Wu; Huan Huang; Na Yin; Yuling Chen; Qiang Yang; Wenjun Zhang; Bingzhi Sun; Ran Sun; et al. (Materials Today Bio)
Periodontal disease stands the leading cause of tooth loss in adults. While scaling and root planning is considered the “gold standard” treatment, it is often insufficient in efficiently eliminating anaerobic bacteria from deep periodontal pockets. In this work, an antibiotic-free and photo-curing hyaluronic acid-Janus (H-Janus) antibacterial pack was developed to inhibit the growth and colonization of residual bacteria within the pockets for reducing the recurrence of periodontitis. Our results demonstrated that a 4 wt% precursor solution of the antibacterial packs could be molded into various shapes by exposure to UV irradiation for less than 1 min, allowing the packs to seamlessly fill the irregular spaces of periodontal pockets. In vitro studies showed that the antibacterial packs gradually released lauric acid and oxygen over 7 days, exhibiting significant anti-biofilm effects against both aerobic and anaerobic bacteria. Notably, animal experiments confirmed that H-Janus antibacterial packs markedly improved the clinical scores in rats with periodontitis by inhibiting bacterial growth, alleviating inflammation, and fostering the regeneration of periodontal tissues. In light of their precise elimination of bacterial colonization and modulation of the infectious microenvironment, the H-Janus antibacterial packs show promising therapeutic potential for preventing the recurrence of periodontal pathogens following scaling and root planning.